Parity-Driven Disparities in Placenta Previa: A Comprehensive Analysis of Obstetric and Perinatal Factors - Fikriye Karanfil Yaman; Sukran Dogru; Huriye Ezveci; Fatih Akkus; Ali Acar (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: This retrospective cohort study aimed to investigate the incidence of known risk factors for placenta previa in primiparous patients and assess the maternal and fetal outcomes associated with this condition in a tertiary hospital setting.